Public procurement and the Economic Partnership Agreements : assessing the potential impact on ACP procurement policies - Woolcock, Stephen (Commonwealth Secretariat [London]GB, 2008)
Describes the nature of rules on government procurement and discusses the distinction between transparency and liberalization. Considers trends in rules on government procurement in other free trade agreements and at the plurilateral level in the Government Procurement Agreement (GPA) of the WTO. Looks at the likely costs to and benefits for the ACP states of adopting rules similar to those adopted in the CARIFORUM-EC EPA text (EPA text). Provides two case studies - South Africa and Uganda to illustrate the impact of any possible rules on the ACP procurement policies. Suggests a number of ways in which the EPA text might be revised to more readily meet the needs and interests of the ACP states.